Health determinants of child malnutrition at the Miraflores Health Center - Vera, Thaily K.; Aguas, Walter A.; Moreira, Heidy J.; Zambrano, Andrea M.; Alejandro, Carlos R. (Revista Gregoriana de Ciencias de la Salud, 2024)
The study carried out at the Miraflores Health Center, Manabí, Ecuador, analyzed the determinants of childhood malnutrition with an exploratory and descriptive approach. The sample included 26 children under five years of age. Through a correlational research design, data were collected through structured interviews, questionnaires and review of medical records, covering biological, sociodemographic and environmental variables. The results revealed that two-year-old children were the most affected, coinciding with the transition period to solid foods. This situation was exacerbated by factors such as the parents’ low educational level, lack of economic resources, and a poorly varied diet. That is, unfavorable socioeconomic conditions were directly associated with a higher prevalence of child malnutrition. Despite access to health services, these factors continue to affect children’s nutrition. It is necessary to implement interventions that improve nutritional education and the resources available to families.